Effect of amplification of the Cap b locus on complement-mediated bacteriolysis and opsonization of type b Haemophilus influenzae. - Noel, G J (1996)
Amplification of the Cap b locus of Haemophilus influenzae occurs frequently in clinical isolates and has been proposed to be a mechanism by which this organism evades host defense. To determine if amplification of this locus affected complement fixation, in vitro studies to determine complement-mediated bacteriolysis and complement-mediated opsonization of an isogenic set of organisms containing 2, 3, and 4 copies of the Cap b locus were performed. Organisms containing 4 copies of the Cap b locus were significantly more resistant to antibody-dependent, classical complement pathway-directed bacteriolysis than were organisms containing 2 copies. Organisms containing 3 copies of this locus exhibited intermediate susceptibility to lysis. Complement-mediated opsonization of these organisms was assessed by determining the degree of binding of bacteria to murine or human macrophages or to nonphagocytic cells transfected with the genes for human Mac-1, the complement receptor type 3. In all three assay systems, organisms containing 4 copies of the Cap b locus bound less well than did organisms containing 2 copies of this locus. Consistent with their decreased susceptibility to lysis and opsonization, organisms with 4 copies of the Cap b locus fixed less C3 than did organisms containing 2 copies. These data demonstrate that amplification of the Cap b locus is associated with decreased susceptibility to complement-mediated lysis and decreased complement-mediated opsonization and suggest that amplification is used by these pathogens to increase their resistance to complement-dependent host defense mechanisms [correction of mecanisms].